DEVELOPMENT AND CHARACTERIZATION OF DOXORUBICIN AND siRNA ENCAPSULATED CHITOSAN NANOPARTICLES - MOMIN, TAIHASEEN; GULBAKE, ARVIND (International Journal of Applied Pharmaceutics, 2020)
Objective: Chitosan nanoparticles (ChNP’s) have been widely studied for drug and gene delivery. In this study, we prepared ChNP’s for co-delivery of doxorubicin (DOX) and siRNA for cancer treatment. Methods: The ionic gelation method was used to develop ChNP’s. The positively charged DOX and negatively charged siRNA encapsulated into ChNP’s. The particle size and zeta potential of the developed ChNP’s were studied by particle size analyzer and morphology was examined by TEM. Encapsulation of DOX in ChNP’s was confirmed by FTIR spectroscopy. The encapsulation efficiency and in vitro release of DOX were studied by UV-Vis spectrophotometry. The siRNA loading into ChNP’s was confirmed by gel retardation assay. Results: The developed ChNP’s showed particle size ranged from 127±6.5 to 215±8.5 nm with zeta potential ranged from 16.5±0.3 to 25.8±0.3. Transmission Electron Micrograph showed DOX and siRNA encapsulated ChNP’s are polydisperse and spherical in nature. FTIR study confirmed the binding of DOX with ChNP’s with absorption peaks at 1016 cm-1, 1316 cm-1, 1412 cm-1, 1645 cm-1 and 3370 cm-1. The TPP:Ch ratio 0.1:0.5 showed the highest encapsulation efficiency 69±3.24%, with initial burst release and then sustained or slow release of DOX. Agarose gel retardation study confirmed the encapsulation of siRNA in ChNP’s by retarded migration of siRNA-ChNP’s in comparison with naked siRNA. Conclusion: The developed ChNP’s successfully encapsulated the DOX and siRNA and showed the sustain release of DOX. In conclusion, our study shown that ChNP’s is having a potential of co-loading of DOX-siRNA as an efficient drug delivery system for the treatment of various cancers such as colorectal cancer, breast cancer etc.